2014
DOI: 10.1589/jpts.26.1013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Smart Phone Use on Dynamic Postural Balance

Abstract: [Purpose] The present study investigated what kind of effect smart phone use has on dynamic postural balance. [Subjects] The study subjects were 30 healthy students in their 20’s who were recruited from a University in Busan, Korea. [Methods] The present experiment was quasi-experimental research which measured the postural balance (Biodex) of subjects while they sent text messages via smart phones in the standing position with the eyes open, and while they used two-way SNS. [Results] There were significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 4 publications
3
20
0
Order By: Relevance
“…Our results regarding the decrease in balance ability agreed with Hyounk [45] and Cho et al [46] who reported that using a smartphone while completing tasks reduced cognitive ability and decreased dynamic balance. Also, Laatar et al [25] found that operating a smartphone increased the center of pressure displacement and impaired the standing postural balance of elderly and young adults.…”
Section: Discussionsupporting
confidence: 91%
“…Our results regarding the decrease in balance ability agreed with Hyounk [45] and Cho et al [46] who reported that using a smartphone while completing tasks reduced cognitive ability and decreased dynamic balance. Also, Laatar et al [25] found that operating a smartphone increased the center of pressure displacement and impaired the standing postural balance of elderly and young adults.…”
Section: Discussionsupporting
confidence: 91%
“…The standing balance in healthy young individuals was also affected by texting in the study of Goddard et al [22]. Cho et al reported a decrease in dynamic balance ability during smart phone texting in healthy young individuals [13].…”
Section: Introductionmentioning
confidence: 96%
“…Since advances in smartphone technology have transformed this hand-held device into an everyday social and/or professional necessity, maintaining an upright posture or walking while talking or texting on the phone are frequently met dual-task demands. The safe use of a phone during daily activities, like standing, walking, stair gait, crossing streets and driving has been studied, since all these acts require cognitive and motor abilities, as well as the division of attention [13][14][15][16][17][18][19]. Texting proved to have a higher detrimental effect on balance, gait and walking behavior in comparison to talking on the phone, increasing the postural sway and decreasing the gait velocity, stride length and cadence [4,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Cho et al (2014), standing balance was measured during smartphone usage in healthy adults in their 20s and 30s. Since a smartphone is portable and easy to use, they used it in a standing position to reproduce the feature that smartphones can be used anytime and anywhere.…”
Section: Discussionmentioning
confidence: 99%